PENGARUH NEGATIF STUNTING TERHADAP PERKEMBANGAN KOGNITIF DAN MOTORIK PADA ANAK BALITA - Linda Andriani; Setia Nisa; Yessy Aprihatin (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2023)
Stunting is a developmental disorder experienced by children due to malnutrition, repeated infections, and inadequate psychosocial stimulation. Several factors cause stunting, namely the practice of giving colostrum and exclusive breastfeeding, consumption patterns of children, and infectious diseases, access and availability of food as well as sanitation and environmental health (World Health Organization, 2015). Stunting at the age of 0-2 years can interfere with children's cognitive, language and motor development (Muhoozi: 2016). The purpose of this study was to determine the negative effect of stunting on cognitive and motor development in toddlers. The research conducted was research using a literature review of the results of research that had been conducted in several regions in Indonesia related to stunting and child development. Source search for journals through Google Scholar in the period 2019 to 2022, and the selected research results include 6 studies from 6 different journals.The results of the study stated that children who were stunted had a 21.58 times greater chance of having below average motor development. In cognitive development related to nutritional status where every increase in the nutritional status of a child's height/age by 1 elementary school, the child's learning achievement will increase by 0.444 and a decrease in the nutritional status of a child's height/age by 1 elementary school, the child's learning achievement will decrease by 0.444.Suggestions in this study are that puskesmas officers assisted by posyandu cadres should be more active in providing counseling and providing consultations about the importance of monitoring toddler growth and development